Non-ideal excitation approach for piezoelectric vibration based energy harvesting - Costa Ferreira, Douglas [UNESP]; Chavarette, Fábio Roberto [UNESP]; Henrique Cerqueira Costa Basquerotto, Cláudio [UNESP]; Peruzzi, Nelson José [UNESP] (Trans Tech Publications, 2014)
Common solution for energy harvester device is project design according harmonic excitation around natural frequency matching excitation source. Environment vibration is random and wide band causing short time of resonance in disagreement of project objectives. Control driven of energy harvesting to take advantage of the higher vibration range can results in greater energy converted. This study investigates a non-ideal excitation behavior and their efficiency in convert electricity via piezoelectric direct effect from the available system energy compared to harmonic excitation source. Numeric evaluation was performed based in bimorph piezoelectric beam in dimensionless consideration. Chaos behavior and harvest energy capability were compared from non-ideal to harmonic excitation. Results demonstrate considerable higher quantity of energy available for non-ideal approach compared to harmonic resonant design and encourages advance study to control and enhance energy from random and wide band vibration source. © (2014) Trans Tech Publications, Switzerland.
Keywords: Efficiency; Energy harvesting; Non-ideal behavior; Random vibration